Uganda chicken genetic resources: II. genetic diversity and population demographic history inferred from mitochondrial DNA D-loop sequences - Yussif, Illyass; Kugonza, Donald Rugira; Masembe, Charles (Frontiers in Genetics, 2024)
The genetic diversity of indigenous chickens which form over 80% of the chicken resources in Uganda is largely not well characterized for their genetic contribution to be well exploited. This study assessed the genetic diversity and population structure of the indigenous chicken population in Uganda, to serve as an essential component for improvement and conservation strategies. A set of 344 mitochondrial DNA (mtDNA) D-loop sequences among 12 Ugandan chicken populations was evaluated. Twenty-eight polymorphic sites, accounting for 4.26% of the total analysed loci of 658 bp, defined 32 haplotypes. Haplotype diversity (Hd) was 0.437 with, nucleotide diversity (π) of 0.0169, while the average number of nucleotide differences (k) was 0.576, indicating a population that is moderately genetically diverse. Analysis of molecular variance found 98.39% (ρ < 0.01) of the total sequence variation among the chicken haplotypes within populations, 1.08% (ρ < 0.05) among populations and 0.75% (ρ > 0.05) among populations within regions. This revealed a subtle genetic differentiation among the populations which appeared to be influenced by population fragmentation probably due to neutral mutation, random genetic drift and/ or balancing selection. All the haplotypes showed affinity exclusively to the haplogroup-E mtDNA phylogeny with haplotype UGA01 signalling an ancestral haplotype in Uganda. Neutrality tests; Tajima's D (-2.320) and Fu's Fs (-51.369) augmented with mismatch distribution to measure signatures of recent historical demographic events supported a population expansion across the chicken populations. The results show one matrilineal ancestry of Ugandan chickens, from the lineage widespread throughout the world, having begun in the Indian subcontinent. The lack of phylogeographic signals is consistent with recent expansion events with extensive within-country genetic intermixing among haplotypes. Thus, the findings in this study hold the potential to guide conservation strategies and breeding programmes in Uganda, given that higher genetic diversity comes from within the chicken population.